Factors Associated with Sexually Transmitted Infection of Patients in Primary Care Unit - Theerawech, Thanpidcha; Bosittipichet, Tatree (Journal of Preventive Medicine Association of Thailand, 2021)
Rising cases of sexually transmitted diseases in Thailand have been increasing at a rapid rate and its condition has caused public health problems, not only in Thailand but also the whole world concern. Studies have shown some contradiction of factors related to sexually transmitted infections and also found zero research from the primary care unit In Phra Nakhon Si Ayutthaya. The purpose of this research is to study factors related to sexual infections of 140 patients in Primary Care by dividing them into 47 people with sexually transmitted infections and 93 non-infected people. The data collection method is interviewing a random group of people from June to October 2020. An interview has included related factors, patient history, personal characteristics, sexual behavior, and sexually transmitted disease. Data analysis of descriptive statistics has included percentage, average, standard deviation, and analytic statistic such as Independent t-test, Chi-square test. The results will be analyzed by Binary Logistic Regression to delineate Multivariate analysis. Researchers have found that major factors related to sexually transmitted infection is patient with sexual infection history and 46.8 percent are Gonococcal infection. In conclusion, the factor associated with sexually transmitted infection was having a previous history of sexually transmitted infection and the factor of personal data was age less than 44 years.